Challenges and Perspectives of Polyhydroxyalkanoate Production From Microalgae/Cyanobacteria and Bacteria as Microbial Factories: An Assessment of Hybrid Biological System - Afreen, Rukhsar; Tyagi, Shivani; Singh, Gajendra Pratap; Singh, Mamtesh (Frontiers in Bioengineering and Biotechnology, 2021)
Polyhydroxyalkanoates (PHAs) are the biopolymer of choice if we look for a substitute of petroleum based non-biodegradable plastics. Microbial production of PHAs as carbon reserves has been studied for decades and PHAs are gaining attention for a wide range of applications in various fields. Still, their uneconomical production is the major concern largely attributed to high cost of organic substrates for PHA producing heterotrophic bacteria. Therefore, microalgae/cyanobacteria, being photoautotrophic, prove to have an edge over heterotrophic bacteria. They have minimal metabolic requirements i.e. inorganic nutrients (CO2, N, P etc), light and can survive under adverse environmental conditions. PHA production under photoautotrophic conditions has been reported from cyanobacteria, the only candidate among prokaryotes, and few of the eukaryotic microalgae. However, an efficient cultivation system is still required for photoautotrophic PHA production to overcome the limitations associated with 1) stringent management of closed photobioreactors and 2) optimization of monoculture in open pond culture. Thus, a hybrid system is a necessity, involving the participation of microalgae/Cyanobacteria and bacteria i.e. both photoautotrophic and heterotrophic components having mutual interactive benefits for each other under different cultivation regime e.g. mixotrophic; successive two module; consortium based etc. Along with this, further strategies like optimization of culture conditions (N, P, light exposure, CO2 dynamics etc.), bioengineering, efficient downstream processes and the application of mathematical/network modelling of metabolic pathways to improve PHA production are the key areas discussed here. Conclusively, this review aims to critically analyze cyanobacteria as PHA producers and proposes economically sustainable production of PHA from microbial autotrophs and heterotrophs in ‘hybrid biological system’.